Analysis of the association between testosterone and cardiovascular disease potential risk factor apolipoprotein B in adult males without cancer: national health and nutrition examination survey 2011-2016 - Chen, Zhiyi; Zhang, Enpu; Gan, Lu; Jiang, Ganggang; Duan, Qilin; Huang, Mou; Li, Huizhen; Huang, Guixiao (Frontiers in Endocrinology, 2024)
Background: Over the years, there has been extensive exploration of the association between testosterone and lipid profiles, yet the precise mechanisms underlying their interaction remain incompletely elucidated. Similarly, there is a dearth of research on the correlation between apolipoprotein B (apoB) and serum total testosterone (TT), particularly within specific populations.We conducted a cross-sectional study to assess the relationship between serum TT concentration and serum apoB concentration. Using the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016, we employed weighted generalized linear models, weighted univariate, weighted multivariate analysis, and smooth curve fitting to assist in exploring the relationship between serum TT and apoB. Serum apoB concentration served as the independent variable, and serum TT concentration as the dependent variable. ApoB was divided into four quartiles -Q1 (<0.7g/L, N=691), Q2 ( ≥ 0.7g/L to <0.9g/L, N=710), Q3 ( ≥ 0.9g/L to <1.1g/L, N=696), and Q4 ( ≥ 1.1g/L, N=708)thereby further solidifying the stable association between the two. Additionally, the application of smooth curve fitting will contribute to a more detailed elucidation of the specific relationship between serum TT concentration and serum apoB concentration under different factors (Drinking, Smoke, Diabetes, Hypertension, and High cholesterol level.).